Effects of cationic polymer on start-up and granulation in upflow anaerobic sludge blanket reactors - Wang, Ying. (2008)
Upflow Anaerobic Sludge Blanket (UASB) process has been receiving widespread acceptance and has been successfully used to treat a variety of industrial wastewaters. The process offers high degree of organics removal, low sludge production, and low energy consumption along with energy production in the form of biogas. However, two major drawbacks of UASB are its long start-up period and deficiency of active biogranules for proper functioning of the process. In this study, the influence of a coagulant polymer on start-up, sludge granulation and the associated reactor performance were evaluated in laboratory-scale UASB reactors. The optimum dosage of cationic polymer as coagulant was also measured by evaluation of the effects of polymer addition on UASB start-up and biogranulation process.